The earth - Parker, Steve, 1952-; Kenyon, Tony (Brookfield, Conn. : Copper Beach Books, 1995)
Through questions and answers, takes a look at Earth from its very beginnings to what it is like today.
Includes index.
School Library Journal, January 1996.
Appraisal-Science Books for Young People, June 1996.
School Library Journal.
Appraisal-Science Books for Young People.
4.8
Keywords: Questions and answers; Questions and answers; Questions and answers; Earth (Planet) -- Miscellanea -- Juvenile literature; Earth (Planet) -- Miscellanea; Earth -- Miscellanea; Earth